Recent fungal diseases of crop plants: Is lateral gene transfer a common theme? - Oliver, Richard; Solomon, P. (AMER PHYTOPATHOLOGICAL SOC, 2008)
A cursory glance at old textbooks of plant pathology reveals that the diseases which are the current scourge of agriculture in many parts of the world are a different set from those that were prominent 50 or 100 years ago. Why have these new diseases arisen? The traditional explanations subscribe to the “nature abhors a vacuum” principle—that control of one disease creates the condition for the emergence of a replacement—but does little to explain why the new pathogen succeeds. The emergence of a new disease requires a series of conditions and steps, including the enhanced fecundity of the new pathogen, enhanced survival from season to season, and spread around the world. Recently, evidence was obtained that wheat tan spot emerged through a lateral gene transfer event some time prior to 1941. Although there have been sporadic and persistent reports of lateral gene transfer between and into fungal plant pathogens, most examples have been dismissed through incomplete evidence. The completion of whole genome sequences of an increasing number of fungal pathogens no longer allows such proposed cases of lateral gene transfer to be dismissed so easily. How frequent are lateral gene transfers involving fungal plant pathogens, and can this process explain the emergence of many of the new diseases of the recent past? Many of the apparently new diseases are dependant on the expression of host-specific toxins. These are enigmatic molecules whose action requires the presence of plant genes with products that specifically encode sensitivity to the toxin and susceptibility to the disease. It is also notable that many new diseases belong to the fungal taxon dothideomycetes. This review explores the coincidence of new diseases, interspecific gene transfer, host-specific toxins, and the dothideomycete class.